Tunnel magnetoresistance in thermally robust Mo/CoFeB/MgO tunnel junction with perpendicular magnetic anisotropy - B. Fang (AIP Advances, 2015)
We report on tunnel magnetoresistance and electric-field effect in the Mo buffered and capped CoFeB/MgO magnetic tunnel junctions (MTJs) with perpendicular magnetic anisotropy. A large tunnel magnetoresistance of 120% is achieved. Furthermore, this structure shows greatly improved thermal stability and stronger electric-field-induced modulation effect in comparison with the Ta/CoFeB/MgO-based MTJs. These results suggest that the Mo-based MTJs are more desirable for next generation spintronic devices.